Pengaruh Economic Value Added dan Market Value Added terhadap Return Saham pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Mustari, Mustari; Oktaviana, Annisa (BUDGETING : Journal of Business, Management and Accounting, 2024)
The purpose of this study was to know the influence of Economic value added and market value added to the stock return on manufacturing company listed in Indonesian Stock Exchange. The time period in this study was taken between 2020 - 2022. This study was by using quantitative methods. The sample in this study was obtained by purposive sampling methods. Based on criteria there were 38 companies that become sample study. The data were collected by the study of documentation and literature. Data analysis technique used descriptive statistical analysis, test requirements analysis, simple linear regression analysis, and multiple linear regression analysis. The results showed: (1) Economic Value Added (EVA) has effect and significant effect on Stock Return, (2) Market Value Added (MVA) has effect and significant effect on Stock Return, and (3) Economic Value Added (EVA) and Market Value Added (MVA) which work simultaneously have a positive effect and significantly toward the Stock Return. Keywords: Economic Value Added (EVA), Market Value Added (MVA), Stock Return.